Evaluation of seagrass beds as a foraging and nursery habitat based on the structure of the fish community in Nusmapi Island, West Papua, Indonesia - EMMANUEL MANANGKALANGI; LUKY SEMBEL; SELVI TEBAIY; AGNESTESYA MANUPUTTY; MINA REGINA RUMAYOMI; PHILIPUS MUSYERI; DODDY SAWAKI; DAUD ORISSU; ABRAHAM WILLIAM MANUMPIL; YUANIKE KABER (Society for Indonesian Biodiversity, 2022)
Abstract. Manangkalangi E, Sembel L, Tebaiy S, Manuputty A, Rumayomi MR, Musyeri P, Sawaki D, Orissu D, Manumpil AW, Kaber Y. 2022. Evaluation of seagrass beds as a foraging and nursery habitat based on the structure of the fish community in Nusmapi Island, West Papua, Indonesia. Biodiversitas 23: 5539-5550. Seagrass beds are one of the ecosystems inhabited by various coastal aquatic fauna, including fish. However, information on the temporal role of this ecosystem for fish fauna, particularly diurnal and nocturnal, is still limited. Therefore, this study was conducted to describe daily variations in the fish species composition, their ecological index, developmental stages, and trophic groups in a seagrass bed on Nusmapi Isl., Manokwari. The species composition differed between day and night sampling periods based on the results obtained from 40 species of fish belonging to 21 families and 7 orders. Furthermore, fish species consisted of three trophic groups (omnivores, carnivores, and herbivores), with omnivores and carnivores dominating during the day and at night by 48.6% and 87.5%, respectively. Species found in seagrass beds majorly consisted of juvenile stage individuals (65.9%). Individual abundance varied from day to night and was mainly found among group-forming species, such as S. spinus, S. trilineata, S. punctatissimum, and M. pralinia. The index of diversity, evenness, and dominance at the two relatively similar sampling times described the overall stability of fish communities in seagrass beds. The results indicate that seagrass beds serve as foraging and nursery grounds for many fish species in coastal waters. In addition, the management and protection of fish biodiversity and coastal fishery resources are affected by the ecosystem function.